L’invention du culte musulman dans l’Algérie coloniale du xixe siècle - Oissila Saaidia (L’Année du Maghreb)
One of the consequences of the conquest of Algeria was to make the French public authorities guardians of the three monotheist religions, and this in a colonial context within the French Empire. To the extent that Colonial Algeria was organized into administrative departments for which laws were in theory enacted by decree, the organization of public worship was dependent upon practices instituted in the home jurisdiction. If the framework seemed obvious for Catholic, Protestant and Jewish worship, despite some reluctance, what was there to say about Islam, the religion of the colonized? The establishment of Muslim worship in colonial Algeria in the nineteenth century was the result of a double bind: on the one hand, the authorities were required to channel Islam, a major obstacle to French rule. On the other hand, French civil society, a multi-confessional society, would have been required to show respect for Islam. To deal with this situation, military and civilian agents of the state developed strategies for dominance based on their own knowledge of the subject populations, using available administrative techniques. This process led us to reflect upon the organization and functioning of Muslim religious services as well as their legal and administrative bases. The present article focuses on the organization and development of Muslim observance from 1830 to 1914, and suggests possible interpretations for worship practices in Algeria and by extension, in France in the early twenty-first century.